The impact of Energy Performance Certificates on building deep energy renovation targets - Charalambides, Alexandros G.; Maxoulis, Christos N.; Kyriacou, Orestis; Blakeley, Erik; Frances, Laura Soto (My University, 2019)
The purpose of this paper is to investigate the effect of Energy Performance Certificates (EPCs) on the renovation of buildings. Thus, through the European project ENERFUND, 2 online web-based surveys were conducted in 12 countries of the European Union. It was shown that the results varied significantly both between countries and age groups and, that, on average, EPCs did play a role both in renovation decisions and whether to rent/buy a certain flat. In addition, this paper presents major key drivers and parameters related to energy renovation investment mobilisation and suggests actions that can contribute to the promotion of investments for deep energy renovation of buildings. Furthermore, it highlights potential benefits and effectiveness of using retrofitting online tools, such as the ENERFUND tool, pinpoints market failures in the building sector and provides suggestions on increasing the deep energy renovation market in Europe.
Keywords: ENERFUND tool; Energy Performance Certificates (EPC); Energy Performance of Buildings Directive (EPBD); EPC awareness; EPC effectiveness on renovation decisions; EPC impact